2010
DOI: 10.1111/j.1095-8649.2010.02540.x
|View full text |Cite
|
Sign up to set email alerts
|

Larval ontogeny and morphology of giant trahira Hoplias lacerdae

Abstract: In the present study, the morphology and behaviour of giant trahira Hoplias lacerdae larvae were investigated, from hatching to complete absorption of the yolk sac, under laboratory conditions. In the first day post-hatching (dph), the larvae presented a big ovoid-shaped yolk sac that underwent regression during larval ontogeny. The mouth opened 3 dph, when the pectoral fins were evident. From this day, the larvae were able to perform sudden bursts of activity and appear to be able to swim a few centimetres be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…Biologically, larval body pigmentation contributes to camouflage them in aquatic substrates (Sanches, Nakatani, & Bialetzki, 1999). In this study, the species presented only dendritic chromatophores, which is similar to what has been recorded in other neotropical species (Cavicchioli & Leonhardt, 1993;Sanches et al, 1999;Bialetzki et al, 2001;Santos & Godinho, 2002;Gomes, Matta, Araujo, Silva, & Zacaro, 2010;Nogueira et al, 2012a). The larvae of Prochilodus corruscans (Santos & Godinho, 1994), Brycon hilarii (Oliveira, Bialetzki, Gomes, Santin, & Taguti, 2012), and Clarias macrocephalus (Morioka, Vongvichith, Phommachan, & Chantasone, 2013) showed only punctate chromatophores, while Trichogaster pectoralis (Morioka, Ito, & Kitamura, 2010) and Zungaro jau (Nogueira et al, 2012a) exhibited punctate and dendritic chromatophores.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Biologically, larval body pigmentation contributes to camouflage them in aquatic substrates (Sanches, Nakatani, & Bialetzki, 1999). In this study, the species presented only dendritic chromatophores, which is similar to what has been recorded in other neotropical species (Cavicchioli & Leonhardt, 1993;Sanches et al, 1999;Bialetzki et al, 2001;Santos & Godinho, 2002;Gomes, Matta, Araujo, Silva, & Zacaro, 2010;Nogueira et al, 2012a). The larvae of Prochilodus corruscans (Santos & Godinho, 1994), Brycon hilarii (Oliveira, Bialetzki, Gomes, Santin, & Taguti, 2012), and Clarias macrocephalus (Morioka, Vongvichith, Phommachan, & Chantasone, 2013) showed only punctate chromatophores, while Trichogaster pectoralis (Morioka, Ito, & Kitamura, 2010) and Zungaro jau (Nogueira et al, 2012a) exhibited punctate and dendritic chromatophores.…”
Section: Discussionsupporting
confidence: 85%
“…The retina of Piabucina pleurotaenia (Allison, 1974), Helostoma temminckii (Souza & Severi, 2000), Auchenipterus osteomystax (Bialetzki et al, 2001), and Mogurnda adspersa (Close, Pusey, & Arthington, 2005) were pigmented at hatching. However, Araújo-Lima (1991), Economou, Daoulas and Psarras (1991), Santos and Godinho (2002), Gomes et al (2010), and Nogueira, Godinho and Godinho (2012) reported for the species that they studied that pigmentation occurs after hatching, as in the species studied here. The reason for these different patterns of retinal pigmentation in Neotropical teleosts still remains unclear (Nogueira et al, 2012).…”
Section: Discussionsupporting
confidence: 51%
“…A large number of studies of GI development in at least a dozen fish species have been published in the past decade (59, 67, 96, 104, 187, 191, 200, 213, 224, 225, 240, 260, 264, 269, 273, 281, 327329, 359, 481, 484, 485) due to their importance in aquaculture, and many studies include newer molecular and gene expression approaches (109, 272). As in birds, a major ontogenetic change in fish is that the source of nutrients and energy necessary to continue larval development changes from the yolk reserves to the ingested food, which is mainly protein and fat in carnivores but higher in carbohydrates in omnivores and herbivores.…”
Section: Matches Of Gi System To Nutritional Changes During Ontogenymentioning
confidence: 99%
“…The development of the caudal fin and its supporting elements helps larvae in their initial swimming movements and more active displacement in the water column, indicating the establishment of caudal propulsion (Omori et al, 1996; Osse & Boogaart, 1999). Conversely, the late development of the pectoral fin will assist in the balance and swimming ability of the larvae (maneuverability) throughout the water column (Gomes et al, 2010).…”
Section: Discussionmentioning
confidence: 99%